2017
DOI: 10.1080/14397595.2017.1317384
|View full text |Cite
|
Sign up to set email alerts
|

Serum interleukin-6 and survivin levels predict clinical response to etanercept treatment in patients with established rheumatoid arthritis

Abstract: Comprehensive measurement of IL-6 and survivin in serum could be served as a convincing biomarker for clinical response in ETN-treated patients with established RA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
12
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 30 publications
4
12
0
2
Order By: Relevance
“…Nevertheless, that group of patients was small, it was noticed that high survivin concentration and its positivity is independent of TNF-α treatment, what is in line with previous observations in adults with RA [7,11,18,21]. On the other hand, some researchers proved that survivin concentration is decreased in TNF-α treatment adult RA responders [24,25]. In our study biologically treated patients with JIA were previously unsuccessfully administered with conventional synthetic DMARDs for a quite long period of time (above one year).…”
Section: Resultssupporting
confidence: 83%
See 1 more Smart Citation
“…Nevertheless, that group of patients was small, it was noticed that high survivin concentration and its positivity is independent of TNF-α treatment, what is in line with previous observations in adults with RA [7,11,18,21]. On the other hand, some researchers proved that survivin concentration is decreased in TNF-α treatment adult RA responders [24,25]. In our study biologically treated patients with JIA were previously unsuccessfully administered with conventional synthetic DMARDs for a quite long period of time (above one year).…”
Section: Resultssupporting
confidence: 83%
“…In our study biologically treated patients with JIA were previously unsuccessfully administered with conventional synthetic DMARDs for a quite long period of time (above one year). Some researchers concluded that survivin could be the marker of DMARDs non-responders [11,23,24]. However, to verify that statement in children, the group of patients with JIA treated with conventional synthetic DMARDs should be also included into the study, what is the area for future studies.…”
Section: Resultsmentioning
confidence: 99%
“…IL-6 at baseline is higher in responders to both etanercept and tocilizumab [37,38]. Furthermore, Shi et al (2017) noted that high serum IL-6 and low serum survivin at baseline was associated with etanercept response with an OR of nearly 20 [37], and Diaz-Torne et al (2017) found the patients showing the greatest response to tocilizumab had a combination of high serum IL-6 and low serum soluble IL-6 receptor [38].…”
Section: Anti-citrullinated Peptide Antibodies and Rheumatoid Factormentioning
confidence: 99%
“…One could ask if the obtained results are su cient to justify the prior conclusions that survivin is the marker of DMARDs non-responders [11,23,24]. Nevertheless, the observations assessing the in uence of treatment on survivin release are con icting.…”
Section: Discussionmentioning
confidence: 95%